REKONSTRUKSI KEBIJAKAN PENDIDIKAN ISLAM BERBASIS KARAKTER, INTEGRASI NILAI QUR'ANI, KEARIFAN LOKAL, DAN INOVASI DIGITAL DI ACEH - Masdar Hilmy; Hamdani (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to reconstruct character-based Islamic education policies in Aceh in response to the challenges of modernity. With the institutional uniqueness of the Dayah Education Office—an institution not found in any other province in Indonesia—Aceh faces a moral crisis and weakening religious identity among the younger generation due to globalization and digitalization. Data show an increase in juvenile delinquency, drug abuse, and social conflict across various regencies and cities in Aceh over the past five years. Using a qualitative approach with a systematic literature review (SLR) method following the PRISMA protocol, this study analyzes 25 journal articles indexed in SINTA and Scopus, as well as policy documents such as the Qanun of Aceh, Law No. 11/2006, and Government Regulation No. 18/2016. The findings reveal a gap between normative policy and the practical implementation of character education, caused by curriculum fragmentation, the suboptimal integration of dayah into the formal education system, weak coordination between the Education Office and the Dayah Education Office, and low adoption of value-based technology. The novelty of this research lies in an integrative policy reconstruction model formulated as: (Qur'anic Values + Local Wisdom + Dayah System) + (Dayah Education Office & Education Office Policies) + (Technology & Innovation) = Adaptive Modern Character Education, positioning the Dayah Education Office as the main integrator. In conclusion, policy reconstruction requires functional harmonization between the Dayah Education Office and the Education Office, as well as a transformation from government toward collaborative good governance.